Hubungan Pengetahuan Ibu Hamil dengan Sikap dalam Melaksanakan Program 1000 Hari Pertama Kehidupan di Wilayah Kerja Puskesmas Monta - Wahidah, Wahidah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The first thousand days of life is a period of growth and development that starts from the formation of the fetus in the womb until the child is two years old. This period is called the golden period or also known as a critical time, which if not utilized properly, permanent damage (window of opportunity) will occur. This research aims to determine the relationship between pregnant women's knowledge and attitudes in implementing the First 1000 days of life program in the Monta health center working area. This type of research is an analytic observation research method with a cross sectional approach. This research was carried out in some of the working areas of the Monta Community Health Center, namely in the villages of Simpasai, Sie and Pela villages. The research was conducted in June 2023. The population in this study were all pregnant women in the working area of the Monta Health Center. The sampling technique uses simple random sampling of 50 respondents. The data analysis carried out was univariate analysis and bivariate analysis. The test used was the chi square statistical test with another alternative test, namely the Fisher Excat test with a significance level of p=0.02, HA was accepted because it was proven that there was a relationship between knowledge of pregnant women and attitudes with p<0.05. It was concluded that there was a relationship between knowledge of pregnant women and attitudes in implementing the 1000 HPK program in the PKM Monta work area. Based on the results of this research, it is best for health workers, especially midwives, to collaborate with health agencies that hold outreach activities in order to increase the knowledge and information of pregnant women about the first 1000 days of life so that they can motivate the attitudes of pregnant women about the first 1000 days of life.